Childhood adversity, allostatic load, and adult mental health: Study protocol using the Avon Longitudinal Study of Parents and Children birth cohort - Finlay, Sabine; Juster, Robert-Paul; Adegboye, Oyelola; Rudd, Donna; McDermott, Brett; Sarnyai, Zoltán (Frontiers in Psychiatry, 2023)
ABSTRACT Introduction: The cumulative burden of chronic stress and life events has been termed allostatic load. Elevated allostatic load indices are associated with different mental health conditions in adulthood. To date, however, the association between elevated allostatic load in childhood and later development of mental health conditions has not been investigated. Methods: Using data from the Avon Longitudinal Study of Parents and Children (ALSPAC), we will calculate allostatic load indices using biomarkers representing the cardiovascular, metabolic, immune, and neuroendocrine systems, at the ages of 9 and 17 years. Bivariate and multivariable logistic regression models will be used to investigate the association between allostatic load and psychiatric disorders in adulthood. Furthermore, the role of adverse childhood experiences as a modifier will be investigated. Discussion: This protocol describes a strategy for investigating the association between elevated allostatic load indices in childhood at the age of 9 years old and psychiatric disorders in adulthood at 24 years old.